Sistem Komunikasi Wearable Yang Menerapkan PCB Fleksibel - Sufianti Munirman (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2023)
The rapid adaptation of Wearable Communication technology to be applied in various fields has shown a remarkable development profile over the past decade. In this research project, a prototype wearable device operating at a frequency of 2.4 GHz was developed using rice husk fiber composite material to construct a flexible PCB Board as a circuit path and shield for IoT component modules and practically tested. This wearable device is designed to transfer video and image streaming data in indoor and outdoor scopes. The sensing object or location captured using the wearable device placed on the user's shirt is connected to an access point and will send the data to a registered server or authorized receiving station. The first trials of the fabricated wearable devices have shown excellent data transmission conducted in two different environments. The maximum communication range between the wearable device and the access point was 87 meters in the indoor test while in the outdoor test the maximum communication distance was 60 meters. During the communication range, the transmission quality degraded so that the sending signal strength during the indoor test was 398 kb/s and the outdoor test was 299 kb/s.